Saberes docentes e estratégias de ensino: as trocas entre professores do Ensino Fundamental - Mariana Costa Lopes da Silva (2009)
This work sought to identify teachers knowledge exchanged among eight primary school teachers during meetings specially dedicated to this research. Other goals were to describe the moments of exchanges, establish a discourse between teachers knowledge and scientific research and contribute to the organization of a teachers knowledge base. In the attempt of reaching these goals, a methodological approach was constructed in three steps: immersion of the researcher in the research locus (exploratory study); focus group and data analysis. By means of the methodological strategy, we united eight primary teachers to discuss real life problem-situations organized by the researcher. We believe to have created through this method a space for dialogue and exchanges among teachers where teachers knowledge could emerge and be made known. The concepts of knowledge and teachers knowledge were based upon Shulman (1986), Tardif (1991; 2000 and 2002) and Gauthier (2006). Through the work of these scholars, we were able to comprehend the concept of knowledge as based upon the rationality of an argumentative nature, a collective construction built from exchanges between agents. These exchanges were defined as sharing, because the exchanges between teachers were not always a give and take situation where agents offer and receive at the same time help and guidance. From data provided by the transcripts of the meetings, analysis was organized in the following categories: Time organization, Space organization, Interaction between teachers and students, Transgressions and Different paces. In each category, teachers speech was reorganized, its validity was demonstrated by its argumentative structure, this structure was confronted by scientific research and by this process we were able to approach teachers knowledge that support and sustain exchanges between teachers. We concluded that the discussion enhanced by real life problem-situations proved to be efficient to create a space for exchanges between teachers. Teachers knowledge is influenced by context where they work and teachers exchange teaching strategies which are supported by teachers knowledge. We hope to have created a space for dialogue between teachers knowledge and scientific research that enabled analysis, critique and thus enrichment of teachers knowledge base.